Understanding E-payment acceptance in Algeria: An extended UTAUT approach with trust as mediator and security as moderator - Ziouache, Alaeddine; Ghani, Amirul Haqeem Bin Abd; Bahaman, Muhamad Abrar Bin (Edelweiss Applied Science and Technology, 2025)
The acceptance of electronic payment (e-payment) systems is crucial for advancing digital transformation and financial inclusion, especially in emerging countries like Algeria. However, the acceptance level remains very low. This study aims to examine the dual influence of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) on customers' acceptance of e-payment services in Algeria. It also investigates the mediating role of Trust and the moderating role of Security within an extended Unified Theory of Acceptance and Use of Technology (UTAUT) framework. A quantitative method was adopted, using a structured questionnaire to collect data from a representative sample of Algerian e-payment users. The study utilized Structural Equation Modeling (SEM) PLS 4.0 to examine mediating and moderating relationships among the study variables. The results show that PEOU and PU have a significant influence on customers' acceptance of e-payment systems. Both relationships are mediated by Trust, illustrating the importance of trust in the acceptance of any technology. Moreover, the Security factor has no moderating effect. This study highlights the importance of developing security levels and building trust to boost e-payment acceptance in Algeria. The findings offer practical guidelines for policymakers and banks to enhance electronic payment methods.